Midgut Malrotation Causing Intermittent Intestinal Obstruction in a Young Adult. (20th May 2014) - Bektasoglu, Huseyin Kazim; Idiz, Ufuk Oguz; Hasbahceci, Mustafa; Yardimci, Erkan; Firat, Yurdakul Deniz; Karatepe, Oguzhan; Muslumanoglu, Mahmut
Abstract : Midgut malrotation is a congenital anomaly of intestinal rotation and fixation that is generally seen in neonatal population. Adult cases are rarely reported. Early diagnosis is crucial to avoid life threatening complications. Here, we present an adulthood case of midgut volvulus as a rare cause of acute abdomen.